MODEL KOOPERATIF TIPE ROTATING TRIO EXCHANGE (RTE) DALAM MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS V SD NEGERI 1501 HURUNG JILOK - Hasibuan, Arfin; Rani Astria Silve; Harahap, Nurhalimah; Hasibuan, Annis (Journal Education Innovation (JEI), 2025)
Based on the research results, it can be concluded that: (1) The mathematical concept understanding ability of students in the pre-cycle obtained a total score of 1330, with an average of 57.83, the highest score of 80 and the lowest score of 40. (2) The mathematical concept understanding ability of students in cycle I obtained a total score of 1710, an average of 74.35, the highest score of 90 and the lowest score of 50. The mathematical concept understanding ability of students in cycle II obtained a total score of 1930, an average of 83.91, the highest score of 90 and the lowest score of 60. The results of observations of the mathematical concept understanding of class V students at SD Negeri 1501 Hurung Jilok in cycle II have increased, namely there are only 20 students or 86.96% who understand the mathematical concept "very good", 3 students or 13.14% who understand the mathematical concept "good", no students who understand the mathematical concept "sufficient", no students who understand the mathematical concept "poor" and no students who understand the mathematical concept "poor". understanding of mathematical concepts is “very lacking”.